Processability and mechanical properties of extensively recycled high density polyethylene. (April 2015) - Oblak, Pavel; Gonzalez-Gutierrez, Joamin; Zupančič, Barbara; Aulova, Alexandra; Emri, Igor
Abstract: In plastics industry it is a common practice to mechanically recycle waste material arising from production. However, while plastics are mechanically recycled, their mechanical properties change. These changes may affect material processing conditions and quality of the end products; therefore they need to be quantified. In this study, mechanical recycling of high density polyethylene (HDPE) was simulated by one-hundred (100) consecutive extrusions cycles. During extrusion, processability of virgin HDPE and its recyclates was studied by recording the processing conditions, i.e. melt pressure and extrusion torque, while after preparation of the recyclates, melt flow index measurements (MFI), small amplitude oscillatory shear tests (rheological properties), and differential scanning calorimetry measurements (DSC) of thermal properties were performed. Also, mechanical properties in solid state were characterized in terms of hardness and modulus measured by nanoindentation, and finally, shear creep compliance was measured to characterize the materials' time-dependent mechanical properties and its durability in solid state. In addition, gel permeation chromatography (GPC) and solubility tests were implemented to study changes in the material structure. The results on rheological and MFI measurements indicate significant structural changes in the material that occurred during the first 30 extrusion cycles. Those changes affect material processability which is as well supported by the recorded processing pressure and torque. On the other hand, processing did not significantly affect material thermal properties. Results on hardness and modulus show deterioration of the material mechanical properties after 10th reprocessing cycle. Similarly, shear creep compliance measurements showed an unfavourable effect of mechanical recycling on the time-dependent mechanical properties, particularly after the 30th extrusion cycle. In addition, results suggested chain branching as a dominating mechanism through first 30 extrusion cycles, domination of chain scission afterwards and also presence of cross-linking after 60th extrusion cycle.